Constraints on a scalar-pseudoscalar Higgs mixing at future e(+)e(-) colliders: An update - Chalov, A.; Likhoded, A.; Rosenfeld, Rogério [UNESP] (American Physical Soc, 2004)
We perform an update of our previous analysis of the constraints on possible deviations of Hb (b) over bar coupling parametrized as (m(b)/v)(a+igamma(5)b), arising from a scalar-pseudoscalar mixing, where the process e(+)e(-)-->b (b) over bar nu(ν) over bar was used. In this paper we include a complete simulation of the process e(+)e(-)-->b (b) over bare(+)e(-) and combine these results to obtain tighter bounds on the deviations of the parameters a and b from their standard model values that could be measured at the Next Linear Collider.